Anonymous Deaths: A Reading of Derek Mahon's "A Refusal to Mourn" and Craig Raine's "In the Mortuary" - Violeta Delgado (Miscelánea: A Journal of English and American Studies)
The aim of this paper is getting an insight into contemporary British poetry through the work of two of its best known poets, Derek Mahon and Craig Raine, by focusing on their treatment of the theme of death. These poets try to approach their theme from a new perspective in order to establish a distance from the tradition that precedes them. Both of them resort to the defamiliairisation of their subject-matter through the recuperation and synthesis of elements coming from different past traditions. They share a common project but their poems are the result of two opposed ways of negotiating the theme of human extinction.